No boys allowed /Marilyn Levinson. - Levinson, Marilyn.
When her father leaves the family to marry a younger woman, eleven-year-old Cassie Landauer feels she can t trust any male, including her best friend, until her great-uncle helps her put the changes in her life in perspective.